2013
DOI: 10.1002/mrd.22150
|View full text |Cite
|
Sign up to set email alerts
|

Luteoprotective roles of luteinizing hormone are mediated by not only progesterone production but also glucocorticoid conversion in bovine corpus luteum

Abstract: Luteinizing hormone (LH) is known as a key regulator of corpus luteum (CL) function, but the luteoprotective mechanisms of LH in the maintenance of bovine CL function are not well understood. The current study investigated if LH increases cell viability and induces cortisol conversion, and if the luteoprotective action of LH is mediated by stimulating the local production and action of progesterone (P4) and/or cortisol. Cultured bovine luteal cells obtained at the mid-luteal stage (Days 8-12 of the estrous cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…A possible mechanism of the enhanced pregnancy rate can be the apoptosis inhibiting effect of GCs on luteal cells, as the maintained luteal function contributes to the survival of the fetus [ 68 ].…”
Section: Janus Face Of Stressmentioning
confidence: 99%
“…A possible mechanism of the enhanced pregnancy rate can be the apoptosis inhibiting effect of GCs on luteal cells, as the maintained luteal function contributes to the survival of the fetus [ 68 ].…”
Section: Janus Face Of Stressmentioning
confidence: 99%
“…The mechanism involved in reentry of luteal cells in cell cycle/apoptosis triggered by PGF is related to proapoptotic cytokines gene expression (IL8, IL1B, TNF and FASL; Atli et al, 2012;Miyamoto et al, 2010). Since intraluteal P4 and cortisol (Kawaguchi et al, 2013) are dependent on LH, and suppress FAS and Caspase-3 mRNA expression (Komiyama et al, 2008;Okuda et al, 2004) the drop of LHR observed at the end of luteal phase in our study may be the key role in luteolysis process.…”
Section: Discussionmentioning
confidence: 53%
“…This study investigates the anti‐apoptotic role of LH during the mid‐luteal phase and its mechanism via intracellular signalling. Previous study showed protective effects of LH against apoptosis via P4 and cortisol production (Kawaguchi et al., 2013). While the role of PKC and cAMP in this matter has been predicted (Tatsukawa et al., 2006), the direct connection between LH, intracellular signalling, P4, as well as cell viability has not been elucidated.…”
Section: Discussionmentioning
confidence: 89%